Ideologi Seni Rupa Indonesia Era 1990-an Pada Karya Tisna Sanjaya - Anggiat Tornado; H. Dadang Suganda; Setiawan Sabana; H. Reiza D. Dienaputra (LP2M ISBI Bandung, 2014)
ABSTRACT The 1990s was the spirit of the New Art Movement undeniable as the embryo of the development of art in the 1990s. Fine art combining all the art that developed (sculpture, painting and printma- king and performance art) by some of the artists who eventually become aesthetic choice. This re- search used emic and etic, semiotic and hermeneutic approach. The research result describes Tisna Sanjaya ideology in the process of creative work tends to raise the issue in this case social critic.Tisna Sanjaya more knows from the source which was appointed to be the theme of his work. Installation art and performace art are an art form that is recognized by Tisna that can communicate directly with the people who were subjected to his art. Tisna Sanjaya as an artist who has the inclination and ideology, art as follows: a) Awareness of the problems though art can not reply on the matter then and there, because art takes time to find the answer. b) Representation of the things that happen to be reported continuously up through artpeople can catch from the issues that are and have happened. Keywords: Ideology, Art in The 1990’s, Tisna Sanjaya ABSTRAK Era 1990-an adalah semangat Gerakan Seni Rupa Baru yang tak dapat dipungkiri sebagai embrio dari perkembangan seni rupa 1990-an. Seni rupa yang memadukan seluruh seni yang berkembangh (antara seni patung, seni lukis dan seni grafis dan performance art) berkembang dan mendapat tem- pat oleh beberapa seniman yang akhirnya menjadi pilihan estetikanya. Penelitian ini menggunakan pendekatan hermeneutik, semiotik dan etik dan emik.Hasil penelitian memaparkan ideology Tisna Sanjaya dalam proses kerja kreatifnya cenderung mengangkat persoalan kritik sosial.. Tisna Sanjaya sebagai seniman yang memiliki kecenderungan dan memiliki ideologi, seni sebagai berikut: a) Penyadaran terhadap persoalan walaupun seni tidak dapat menjawab dari persoalan tersebut saat itu juga , karena seni membutuhkan waktu untuk me- nemukan jawabannya. b) Representasi dari hal yang terjadi yang harus dikabarkan terus menerus hingga lewat seni orang dapat menangkap dari persoalan yang sedang dan pernah terjadi. Kata kunci: Ideologi, Seni Era 1990-an, Tisna Sanjaya